QBD-BASED DEVELOPMENT AND EVALUATION OF TIME-DEPENDENT CHRONOPHARMACEUTICAL DRUG DELIVERY SYSTEM OF AMOXICILLIN TRIHYDRATE FOR MANAGEMENT OF BACTERIAL INFECTION (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The present studies discuss about the quality by design (QbD)-based development and evaluation of chronomodulated release drug delivery system of amoxicillin trihydrate for management of bacterial infection. Initially, target product profile was defined and critical quality attributes were earmarked. Risk assessment study was performed for identifying the critical material attributes. Preformulation studies were carried out, and direct compression method was employed for the preparation of bilayer matrix tablets containing a delayed and a sustained release layer for preliminary optimization. Systematic formulation optimization was carried out using central composite design by selecting the concentration of Eudragit-L100 D55 and HPMCK4M. Mathematical modeling was performed and optimized compositions of the polymers were identified from the design space. Moreover, the prepared bilayer tablets were evaluated for various tablet properties including in vitro drug release study, release kinetics evaluation and characterized for FTIR, DSC, XRD, SEM studies, in vitro was-off test, antimicrobial assay and accelerated stability studies. In a nutshell, the present studies indicated the supremacy of designing a chronomodulated release bilayer tablet formulations of amoxicillin trihydrate for effective management of bacterial infections.